ANALISIS STABILITAS LERENG DALAM PENENTUAN BATAS PENAMBANGAN PADA ZONA 4 TAMBANG ANDESIT PT. BINTANG SUMATERA PASIFIC, KECAMATAN PANGKALAN KOTO BARU, KABUPATEN 50 KOTA, SUMATERA BARAT - Reno Putra; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. The weak areas that affect slope stability at PT. Bintang Sumatera Pacific. Slope safety factors at the mining location must be considered because of mining activities carried out on these slopes. Slope geometry with upper slope 10.31m and 20.88m down slope with 37.14m width and 82 ° slope. The slope stability analysis used is the general limit equilibrium method. As a result of the research, the following conclusions were drawn. Analysis of rock mass characteristics based on RQD and RMR analysis with rock types at the study location classified in class II on both slopes. Second, the type of landslide potential at the research location is direct toppling of 39.13% on the upper slopes and 29.91% on the lower slopes. Third, the results of the actual slope analysis as a whole obtained the value of FK = 3.478 (natural conditions) and FK = 2.684 (saturated conditions). Fourth, to obtain the final geometry of the safe slope, the geometric simulation of the slope is carried out by reducing the height of the lower slope based on the blasting depth by 6m. From the three simulations carried out, the final geometry of the safe slope is obtained, namely the slope height of 31.19m and slope of 82 °.The overall FK obtained in saturated conditions was 1.535 in safe conditions. Keywords:  Slope Stability Analysis, RQD, RMR, General Limit Equilibrium, Direct Toppling